Pengaruh Pemberian Kompos Ampas Tahu dan Pupuk NPK Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays Saccharata Sturt) - Fuaddi Nur Huda; Adiwirman Adiwirman; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the influence of tofu compost, NPK fertilizer and its interaction and to get the dose which gives the highest influence on growth and production of sweet corn plant (Zea mays Saccharata Sturt). This research was conducted at Experimental Garden of Agriculture Faculty of Riau University, Campus Bina Widya KM 12,5 Simpang Baru Village, Tampan Sub District, Pekanbaru City for four months starting from April to July 2017. This research was conducted experimentally using Randomized Block Design ) Factorial, which consists of 2 factors. First : The dosage compost (K) is:      K0 = 0 ton.ha-1, K1 = 10 ton.ha-1, K2 = 20 ton.ha-1.Second : Dose of NPK 16: 16: 16 fertilizer (P): P1 = 250 kg.ha-1 NPK, P2 = 300 kg.ha-1 NPK, P3 = 350 kg.ha-1 NPK. The results showed that tofucompost's dosage of 20 ton.ha-1 and NPK 350 kg.ha-1 fertilizer gave the highest yield on weight parameters by the cob without weight, length of the cob, number of seedsrow of cob, number of seeds row and fresh cob with the best quality of cornhusk.Keywords:Compost of tofu dregs, NPK fertilizer, sweet corn plant.